Trichosporon asahii Urinary Tract Infection in a Patient with Severe COVID-19. (17th December 2021) - Cronyn, Verschoyle; Howard, John; Chiang, Leslie; Le, Lisa; Tims-Cook, Zandraetta; Gertz, Alida M
Abstract : Trichosporon asahii is a yeast-like basidiomycete that is an emerging opportunistic infection in immunocompromised patients. Urinary tract infections due to T. asahii are rarely reported in the literature and typically seen only in immunocompromised patients. In addition to being immunocompromised, critically ill COVID-19 patients often have prolonged exposure to antibiotics, corticosteroids, and Foley catheters, which further increases their susceptibility to infection with T. asahii. There are limited case reports documenting successful treatment of T. asahii among hospitalized patients, particularly among COVID-19 patients, in the literature. Therefore, it is important that successful treatment regimens be reported. Here, we report a case of T. asahii urinary tract infection successfully treated with fluconazole and voriconazole in a 73-year-old male recovering from COVID-19. Urinary tract infections with T. asahii should be considered in persistently febrile COVID-19 patients with fungal urinary tract infections since prompt recognition and treatment can reduce the risk of disseminated disease and early mortality.